PENGGUNAAN SOSIAL MEDIA DALAM PELAYANAN PUBLIK DI KANTOR DESA CIBADUNG KECAMATAN GUNUNG SINDUR, KABUPATEN BOGOR - Zaki Zainal Arifin; Suwandi Suwandi; Turkamun Turkamun (PENGABDIAN SOSIAL, 2023)
ABSTRACT  The purpose of this Community Service activity is to provide knowledge and understanding to village staff/apparatuses at the Cibadung Village Office, Gunung Sindur District, Bogor Regency. The results of this extension are expected to be implemented by village officials in carrying out their duties of administering village government, implementing village development, community development and empowering village communities by using all aspects to fulfill and implement public services, one of which is by using social media in the implementation of services.This counseling needs to be carried out so that village staff/apparatuses understand their functions in accordance with Law No. 6 of 2014 concerning Villages so that they can carry out their duties professionally, efficiently, and effectively, openly and responsibly. In Article 18 paragraph (7) it is explained that the implementation of village government aims to improve public services for village community members in order to accelerate the realization of general welfare, increase the socio-cultural resilience of village communities in order to create village communities that are able to maintain social unity as part of national security, advance the village economy as well as overcoming national development gaps and strengthening rural communities as development subjects.Universities in their position as community partners have a moral obligation to provide guidance. For this reason, community service activities are carried out to provide training and additional knowledge about social media which is directed at supporting the implementation of good public services.The method used in this activity is the Participatory Learning and Action (PLA) approach or the Participatory Learning and Practice Process. PLA is a method of community empowerment which consists of a learning process (training, brainstorming, and discussion) on topics such as maximizing the functions of e-mail, WhatsApp, Instagram and other social media and afterwards followed by real actions or activities that are relevant to the material presented about the material. social media (Mardikanto and Soebiato, 2012:203). This service activity is carried out in the form of counseling with assistance.The target of this activity is that village staff/apparatuses have qualified skills in using social media for the implementation of public services so that they can support the smooth running of public services at the sub-district office, and it is hoped that they will be able to produce better servants than before. Community service activities (PKM) are planned to be carried out for three days from 24-26 October 2022. With the theme; THE USE OF SOCIAL MEDIA IN PUBLIC SERVICES IN THE CIBADUNG VILLAGE OFFICE, GUNUNG SINDUR DISTRICT, BOGOR DISTRICT.Keywords: Social Media, Public Services, Cibadung Village